THE RESULT OF THE EXPERIMENT DETERMINING THE BREAKING FORCE OF GRAIN HULL GROWN IN THE CONDITIONS OF MONGOLIA DEPENDING ON ITS MOISTURE (World Science, 2023)
The objectives of the long-term development policy of Mongolia "VISION-2050" include scientific and knowledge-based development of agricultural production with the sight of sustainable development, the ability to transform knowledge into practice, the introduction of advanced technologies and innovations, the extension of agricultural raw materials and products in a foreign market, suspending the import of certain types of raw materials and products, and increasing exports.То implements the policy, it is necessary to carry out a scientific study on the process of hulling technology for all types of grain production and to select the key parameters of design and technology of the huller machine, the breaking force of grain hull depending on its moisture was determined by experimenting 100-grain seeds with the experiment being repeated 3-5 times in laboratory environment. The result of the study is presented by using mathematical statistical analysis methods on the numerical data.